Bleaching of Some Vegetable Oils with Acid-Activated Jordanian Bentonite and Kaolinite - R. BAYARI, OMAR; M. MUSLEH, SALEM; F. TUTUNGI, MAHA; W. DERWISH, GHAZI (Asian Journal of Chemistry, 2010)
Acid activated Jordanian bentonites and kaolinites (employing hydrochloric, sulfuric, phosphoric and acetic acids) are used for the bleaching of corn, soybean and sunflower oils. The results showed that in general the Jordanian bentonites but not kaolinites, compared favourably with the industrial commercial bleacing earth. The sulfulric acid activated sample showing uniformly best bleachability property. Freundlich's isotherms showed that the acid activated Jordanian bentonites displayed superior adsorption strength, but inferior adsorption capacity, when compared with commercial bleaching earths. This could be due to the low montmorillonite content but high acidity of the activated Jordanian bentonites, which are therefore quite suited for the initial bleaching of pigmented vegetable oils.